Early metabolic and hemodynamic indicators of kidney dysfunction in mice offspring from parental low protein diet - Fabiola Diniz; Francesca Edgington-Giordano; Samir S. El-Dahr; Giovane G. Tortelote (SpringerOpen, 2024)
Abstract Background Parental malnutrition, particularly a low-protein diet (LPD), causes oligonephropathy at birth and predisposes offspring to hypertension and chronic kidney disease later in life. The onset of adult kidney disease varies based on genetics and environmental factors, often with subclinical alterations in kidney function being overlooked. This study aimed to examine changes in kidney morphology before significant kidney function decline in the offspring of mice fed a low-protein diet. Methods Using a combination of histological analysis, kidney metabolic and hemodynamic panel assessments, and advanced statistical techniques such as Linear Discriminant Analysis (LDA) and Principal Component Analysis (PCA), we investigated the initial impact of a maternal low-protein diet (LPD) on kidney development and function. Our study utilized 12-week-old F1 mice from F0 parents fed either a low-protein diet (LPD) or a normal-protein diet (NPD) before the onset of hypertension. Results The offspring (F1 generation) of parents (F0 generation) fed an LPD show reduced body weight from birth to P20. The kidney weight was also reduced compared to F1 offspring from parents fed an NPD. At 12 weeks of age, body weight normalized, but kidney weight remained low. Offspring of parents fed an LPD displayed abnormal kidney morphology, including dilated tubules, oligonephropathy, and fluid-filled cysts which had worsened with age. A kidney metabolic panel analysis at 12 weeks revealed a slight but consistent increase in urine albumin, plasma creatinine, mean urea, and BUN concentrations. Although no significant changes in hemodynamic variables were observed, 2/12 mice, both males, showed alterations in systolic blood pressure, suggesting sex-specific effects when comparing F1 mice from F0 fed either diet. Overall, kidney metabolic changes were strongly correlated to parental LPD. Conclusion Our findings indicate that significant kidney damage must accumulate in the F1 generation from parents fed an LPD before any detectable changes in blood pressure occur. Our study suggests that small variations in kidney metabolic function may point to early kidney damage and should not be overlooked in the offspring of these malnourished mice and likely humans.